Kanaima Distant, 1909: descrição de uma nova espécie (Hemiptera, Auchenorrhyncha, Cercopidae, Tomaspidinae) - Stancik,Juliane Franzen (2003)
Kanaima Distant, 1909: description of a new species (Hemiptera, Auchenorrhyncha, Cercopidae, Tomaspidinae). A new species, Kanaima dubia, is described from São José dos Pinhais, Paraná, Brazil. It is similar, in general aspect, to Kanaima fluvialis (Lallemand, 1924).